The investigation on effect on terrain in wind related disaster - Nik Nor Amalina, Mustafa (2014)
Topographic amplification of wind speed has been a significant contributing factor in the past experience. The concerning in actual wind speeds at wind-induced damage to buildings and structures incident spot are increased recently. Areal assessment of wind speeds due to topography effect need to investigate. The specific objectives of this research are as follows: To create a database of wind-induced damage and to quantify the wind speed at the incident spots. The wind-induced damage location and surrounding topography of spot had been map using Geographical Information System (GIS). Further, hill shape factor of topography at the incident spots had been calculated, based on MS 1553:2002. Finally, actual wind speeds at the spot were determined. The result show topography will increase the wind speed that effect building and structure at the spot. Therefore the considerations due to the topography effect in wind loads at design stage are vital.